Investigating G-protein coupled receptor signalling with light-emitting biosensors - Demby, Alexander; Zaccolo, Manuela (Frontiers in Physiology, 2024)
G protein-coupled receptors (GPCRs) are the most frequent target of currently approved drugs and play a central role in both physiological and pathophysiological processes. Beyond the canonical understanding of GPCR signal transduction, the importance of receptor conformation, beta-arrestin (-arr) biased signalling, and signalling from intracellular locations other than the plasma membrane is becoming more apparent, along with the tight spatiotemporal compartmentalisation of downstream signals. Fluorescent and bioluminescent biosensors have played a pivotal role in elucidating GPCR signalling events in live cells. To understand the mechanisms of action of the GPCR-targeted drugs currently available, and to develop new and better GPCR-targeted therapeutics, understanding these novel aspects of GPCR signalling is critical. In this review, we present some of the tools available to interrogate each of these features of GPCR signalling, we illustrate some of the key findings which have been made possible by these tools and we discuss their limitations and possible developments.